Процес формування стратегії SMM-просування: особливості та етапи створення - Шандрівська, О. Є.; Соколов, Ю. С.; Shandrivska, O. Y.; Sokolov, Y. S. (Видавництво Львівської політехніки, 2022)
У статті розкрито специфіку використання соціальних мереж як бізнес-інструменту з просування товарів та послуг у контексті дослідження процесу формування стратегії SMM-просування для розвитку бренда. Основними чинниками актуалізації розгортання бізнесу в онлайн-форматі визнано загострення внутрішньогалузевої конкурентної боротьби і проявів мегатрендів інформатизації та індивідуалізації потреб споживачів в умовах поширення пандемії Covid-19. Визначено чинники успішного просування медіаресурсу в соціальних мережах. Ідентифіковано та обґрунтовано зміст етапів формування стратегії SMM-просування для розвитку бренда.

The article reveals the specifics of using social networks as a business tool for promoting goods and services. Factors of counteraction and successful promotion of the media resource in social networks are identified. The content of the stages of forming an SMM promotion strategy for brand development is identified and justified. The authors hypothetically suggest that there are grounds for increased competition in the commodity markets due to the manifestations of modern megatrends and the need to adapt to the consequences of the spread of the Covid-19 pandemic. Given the complication of the economic situation of commodity markets, the curtailment of online mobility of consumers who have turned to meeting basic needs if necessary, it has become relevant for enterprises to transfer business to an online format through the use of SMM promotion tools. The purpose of the article is to study the process of forming an SMM promotion strategy for business by stages, to reveal the content of its individual stages and factors of influence in the context of increased competition and saturation of commodity markets. Taking into account a certain goal in the work, the task was set and completed: * analyze the content based on the specifics of the promotion process in social networks, taking into account the aggravation of competition in commodity markets; * reveal the content of the stages of forming an SMM promotion strategy and analyze them, taking into account the specifics of enterprises' activities online. The paper uses the following general scientific and special methods of conducting economic research: abstract-logical (theoretical generalizations and formation of conclusions); inductive and deductive (collection, systematization and processing of information); graphic (visual representation of research results); monographic (systematization of evaluation of criteria for the effectiveness of SMM promotion of goods of enterprises); analytical (analysis of existing tools for promoting goods of enterprises) and others. The paper analyzes the problems of forming SMM promotion in social networks. In particular, attention is paid to the relevance of the problem of using social networks, the study of the stages of developing an SMM strategy based on the behavioral characteristics of users of social networks. A study of existing methods of SMM promotion was conducted, among which targeted advertising, interaction with users, and advertising in communities were considered. It is concluded that the process of forming an SMM promotion strategy consists of the following stages: formulation of the goals and objectives of SMM promotion of goods/brand/enterprise, which are aimed at identifying, focusing and developing key advantages for promoting a unique offer and communicating them to the target audience of users; analysis of the media space in social networks (competitive environment, target audience and product/brand/enterprise promotion offers): competitive analysis and selection of brand positioning features (benefits, key advantages, loyalty) among others; analysis of users and their segmentation by socio-economic, demographic, behavioral and other parameters, forming a user profile, assessing the potential of user involvement in SMM promotion; studying the presence of a product/brand/enterprise offer in the online information space and determining its unique differences; formation of alternative SMM strategies-promotion of a unique sales offer and selection of the optimal one among alternatives (taking into account the format of the final product, budgeting SMM promotion, choice of platform among alternative to promote the SMM project, choice of SMM promotion methods); formation of a content concept; implementation of an SMM campaign; monitoring of effectiveness according to the KPI related to social networks, KPI tracked in Google Analytics, KPI related to the company's profit; KPI related to assessing the completeness of using the potential of online communications and the levels of its effectiveness; coordination with goals and regulation of inconsistencies.
The process of forming an SMM promotion strategy: features and stages of creation
Keywords: бренд; SMM-просування; цільова аудиторія; стратегія SMM просування; стратегія контенту; онлайн-просування; brand; SMM promotion; the target audience; SMM strategies-promotion; strategy of content; online-promotion; 338